Concrete composites reinforced with graphene oxide nanoflake (GONF) and steel fiber for application in rigid pavement. (December 2022) - Cho, Byoung Hooi; Nam, Boo Hyun
Abstract: In this study, the effects of graphene oxide nanoflake (GONF), a low-cost carbon-based nanomaterial, on mechanical properties and flexural fatigue performance of different concrete mixtures (i.e., normal concrete (CTRL), GONF mixed concrete (GO-C), steel fiber reinforced concrete (SFRC), and GONF mixed SFRC (GO-SRC)) were investigated, and the feasibility of implementation of the mixtures in rigid pavement was examined. The results demonstrate that the fatigue performances of CTRL and SFRC are enhanced by GONF of 0.1% by weight of cement although the static mechanical strength and modulus of elasticity are barely affected. While the maximum tensile stresses and deflections of concrete slabs calculated by Westergaard's solution show almost similar values regardless of the mixture types and slab thicknesses, the maximum principal stresses induced in the slabs computed by finite element (FE) analysis were increased by SFs about 7–12% under the vehicle and environmental loading conditions in accordance with the slab thickness. In both cases, however, the GONF and SFs reduced the stress ratio, affecting the fatigue performance. The fatigue models of the mixtures for an application in rigid pavement are proposed based on Mechanistic-Empirical Pavement Design Guide, and scenario studies show that the GONF of 0.1% can significantly reduce the slab thickness by 12.6–14.6% regarding the pavement service life of 25–50 years.